Synovial Chondromatosis of the Ankle Joint: Clinical, Radiological, and Intraoperative Findings - Sedeek Mohamed Sedeek; Q. Choudry; S. Garg (Case Reports in Orthopedics)
Synovial chondromatosis, also termed synovial osteochondromatosis, is a rare benign disorder characterized by the presence of cartilaginous nodules in the synovium of the joints, tendon sheaths, and bursae. It most commonly involves large joints, such as the knee, hip, and shoulder, but its presence in smaller joints has also been reported. Nevertheless, ankle involvement is unusual. The diagnosis is commonly made following a thorough history, clinical, physical, and radiographic examination. We report a case of a young patient with primary synovial chondromatosis of the ankle joint and present the clinical, radiographic, and intraoperative findings.